ANALISIS ANTREAN DALAM USAHA MENINGKATAN PELAYANAN PADA CREDIT UNION KHATULISTIWA BAKTI DI PONTIANAK - Maran, Maran (MABIS, 2012)
Credit Union Khatulistiwa Bakti Di Pontianak is a credit union, is currently popular and very interested in the community. The purpose of this study was to determine the role of the queue system in service on Credit Union Equatorial Consecrated in Pontianak. This study uses deskripti. Data collection was performed using the method of observation, and interviews. Data were analyzed using the queue method calculation formula. From the results of this study concluded that the policy of the Credit Union Khatulistiwa Bakti Di Pontianak able to give satisfaction to the members who make transactions, both deposits and transaction security be at the service credit. Credit Union Khatulistiwa Bakti Di Pontianak should put four cashiers during peak hours such as 10:00 to 11:00 pm at utilizing other employees in the finance department.